2021
DOI: 10.1037/xge0001039
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talker generalization in the perception of nonnative speech: A large-scale replication.

Abstract: Speech perception depends on the ability to generalize previously experienced input effectively across talkers. How such cross-talker generalization is achieved has remained an open question. In a seminal study, Bradlow & Bent (2008, henceforth BB08) found that exposure to just 5 min of accented speech can elicit improved recognition that generalizes to an unfamiliar talker of the same accent (N = 70 participants). Cross-talker generalization was, however, only observed after exposure to multiple talkers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 118 publications
(266 reference statements)
2
8
0
Order By: Relevance
“…However, across the three experiments, we demonstrate that II learners can resist changes in F0 for generalization tests performed immediately and one week after training, suggesting that auditory II category representations are not tightly linked to low-level dimensions irrelevant to discriminating category members. Changes in F0 analog changes in talker (e.g., Bradlow and Bent, 2008;Xie et al, 2021). This finding is consistent with previous auditory and speech category learning studies that showed talker-independent category representations emerged at both behavioral and neural levels during training (Bradlow and Bent, 2008;Feng et al, 2019Feng et al, , 2021cJohnson and Sjerps, 2021;Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, across the three experiments, we demonstrate that II learners can resist changes in F0 for generalization tests performed immediately and one week after training, suggesting that auditory II category representations are not tightly linked to low-level dimensions irrelevant to discriminating category members. Changes in F0 analog changes in talker (e.g., Bradlow and Bent, 2008;Xie et al, 2021). This finding is consistent with previous auditory and speech category learning studies that showed talker-independent category representations emerged at both behavioral and neural levels during training (Bradlow and Bent, 2008;Feng et al, 2019Feng et al, , 2021cJohnson and Sjerps, 2021;Xie et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Changes in F0 analog changes in talker (e.g., Bradlow and Bent, 2008;Xie et al, 2021). This finding is consistent with previous auditory and speech category learning studies that showed talker-independent category representations emerged at both behavioral and neural levels during training (Bradlow and Bent, 2008;Feng et al, 2019Feng et al, , 2021cJohnson and Sjerps, 2021;Xie et al, 2021). In speech perception, native listeners can maintain perceptual constancy while facing various types of acoustic and perceptual variabilities (Bradlow and Bent, 2008;Feng et al, 2018Feng et al, , 2021a, suggesting exceptional generalization ability to overcome the "lack-of-invariance" challenge.…”
Section: Discussionsupporting
confidence: 87%
“…It is also shared with the majority of work on talker-specific accent adaptation: both experiments analyzed here employed a single non-native accented talker. There is now evidence that the results of such experiments can depend on the specific talker (for evidence and discussion, see Xie et al, 2021b). Moving forward, the same models employed here for talker-specific adaptation can be used to understand adaptive changes in listeners' perception and categorization following exposure to multiple talkers, or listeners' ability to generalize previously experienced input to unfamiliar talkers (for discussion and model development, see Kleinschmidt and Jaeger, 2015, Part II.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…To mitigate any talker-specific effects in this new sample of talkers (see e.g. Xie et al, 2021), we also counterbalanced the talkers across the taskswhich was not something that was done in the original. Finally, our statistical analyses differed substantially from the original (details below).…”
Section: Methodsmentioning
confidence: 99%
“…While the original studies did not use counterbalancing but instead used a fixed talker for single-talker tasks, we counterbalanced the assignment of talkers and items to avoid unwanted talker-or item-specific effects (see e.g. Xie et al, 2021). In the HV condition, stimuli from the five talkers were presented on separate days in line with the original studies.…”
Section: Designmentioning
confidence: 99%